2003
DOI: 10.1116/1.1624250
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam lithography process using radiation sensitive carboxylate metalorganic precursors

Abstract: A bilayer process has been developed for electron beam lithography using radiation sensitive metalorganic precursors as imaging layers in conjunction with organic planarizing layers. Upon electron beam irradiation, the precursor is converted to a metal oxide which serves as an etch mask for subsequent pattern transfer through the planarizing layer. In this article, a titanium(n-butoxide) 2 (2-ethylhexanoate) 2 precursor was investigated that exhibits sensitivity and contrast of 495 C/cm 2 and 2.75, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Metal 2-ethylhexanoates are used as precursors to metal oxides [22], and are converted using methods such as thermal decomposition [23][24][25], exposure to light [26][27][28][29][30][31][32][33], or exposure to high-energy electron [34][35][36] or ion [31] beams. Our previous efforts have focused on the latter two methods, as they are conducive to the direct patterning of metal oxide [26,[28][29][30] and nanocomposite [27,37] thin films onto a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Metal 2-ethylhexanoates are used as precursors to metal oxides [22], and are converted using methods such as thermal decomposition [23][24][25], exposure to light [26][27][28][29][30][31][32][33], or exposure to high-energy electron [34][35][36] or ion [31] beams. Our previous efforts have focused on the latter two methods, as they are conducive to the direct patterning of metal oxide [26,[28][29][30] and nanocomposite [27,37] thin films onto a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…2(a)) that the films were partially crystallized with a preferred <111> orientation due to (111) plane matching with Pt substrate [8]. Jeyakumar et al [9] and Saifullah et al [10] report that an exposure of electron beam sensitive precursor films to an electron beam results in the cleavage of organic ligands from the central metal atom and converts the metal atom to a metal oxide. In our case, the oxygen content was enough for the metal to convert to a metal oxide during the electron beam exposure because the ratio of metal (Pb, Zr, and Ti) to oxygen was 1 to 5 in the PZT starting precursors.…”
Section: Resultsmentioning
confidence: 96%
“…It has been demonstrated that feature sizes below 100 nm can be achieved using similar metallorganic precursor films in conjunction with electron beam lithography. 25,26 Following exposure and development, the resulting oxide features were examined by SEM. The features were found to be slightly wider at the top than at the bottom.…”
Section: Resultsmentioning
confidence: 99%